Capital Controls : Country Experiences with Their Use and Liberalization - Ariyoshi, Akira (Occasional Papers; Occasional Paper ;, 2000)
This paper examines country experiences with the use and liberalization of capital controls to develop a deeper understanding of the role of capital controls in coping with volatile capital flows, as well as the issues surrounding their liberalization. Detailed analyses of country cases aim to shed light on the motivations to limit capital flows; the role the controls may have played in coping with particular situations, including in financial crises and in limiting short-term inflows; the nature and design of the controls; and their effectivenes and potential costs. The paper also examines the link between prudential policies and capital controls and illstrates the ways in which better prudential practices and accelerated financial reforms could address the risks in cross-border capital transactions.